Neuropsychological and neuroradiological correlates in Huntington's disease. Issue 10 (October 1988) - Starkstein, S E; Brandt, J; Folstein, S; Strauss, M; Berthier, M L; Pearlson, G D; Wong, D; McDonnell, A; Folstein, M
Abstract : Measurements of cortical and subcortical atrophy were made on CT scans of 34 patients with Huntington's disease. Significant correlations were found between the bicaudate ratio (BCR) and an eye movement scale (r = 0.44, p less than 0.01), and activities of daily living scale (r = 0.57, p less than 0.001) and the Mini-Mental State Exam (r = 0.49, p less than 0.01). No correlations were found between BCR values and severity of chorea or voluntary motor impairment. A detailed neuropsychological evaluation of 18 Huntington's disease patients showed significant correlations between the BCR and Symbol Digit Modalities test (r = 0.65, p less than 0.01), and parts A (r = 0.72, p less than 0.001) and B (r = 0.80, p less than 0.0001) of the Trail Making Test. These data support work in primates that demonstrates the role of the caudate nucleus in cognitive and oculomotor functions, but not in motor control (which is governed by putamino-subthalamic systems). The specific cognitive skills correlated with caudate atrophy in Huntington's disease are those reported in primate work to be served by the frontal-caudate loop system: eye movements, conceptual tracking, set shifting and psychomotor speed.